Exsanguination and tissues fixation in embalmed corpses (Gaceta de Ciencias Veterinarias, 2018)
Animal exsanguination under general anesthesia is part of procedure to prepare corpses for teaching in Veterinary Anatomy. In order to assess whether the bleeding during this process influences tissue fixation, a study was made. The animals were subjected to general anesthesia with propofol (4-6 mg/kg), exsanguination was performed by incision of the common carotid artery and amount of blood collected was measured. Once the death was verified, corpses were perfused with a fixing-conservative solution by arterial way, and were kept at room temperature for 24 hours and then they were refrigerated at 4 °C about one week. After this period they were dissected and eviscerated to perform macroscopic evaluation. Aspects evaluated were degree of fixation of lungs, heart, liver, spleen, intestines, kidneys and muscles, as well as, presence or absence of putrefaction odor. Results showed that animals had an exsanguination average of 4.04%, the organs with highest percentage of bad fixation were liver, spleen, kidneys and intestines. Statistical analysis was performed whit the SPSS 19.0 software using contingency tables (Somers gamma and d coefficients), which showed that there are no statistically significant differences for fixation between animals that lost more blood and the who lost less blood. We had concluded that the amount of blood lost during exsanguination has no significant influence on the degree of corpse tissue fixation.
Keywords: Exsanguination; fixation; conservative solution; formaldehyde